The changing epidemiology and aetiology of hepatocellular carcinoma from 1969 through 2013 in Alaska Native people. (16th June 2016) - Connelly, Marc; Bruce, Michael G.; Bulkow, Lisa; Snowball, Mary; McMahon, Brian J.
Abstract: Background & Aims: Alaska Native people have an increased rate of hepatocellular carcinoma compared to the United States population. Viral hepatitis is a risk factor for malignancy and the leading cause of hepatocellular carcinoma in Alaska. With the introduction of hepatitis B immunization in 1982, as well as the emergence of hepatitis C virus in this population, the epidemiology and aetiology of hepatocellular carcinoma in Alaska have changed. Methods: Using the Alaska Native Tumor Registry, all cases of viral and non‐viral hepatocellular carcinoma occurring from 1969 through 2013 were identified and reviewed. Incidence rates per 100 000 population were calculated for hepatocellular carcinoma overall and by aetiological category. Results: One hundred and fifty‐two cases of hepatocellular carcinoma were identified in 148 Alaska Native persons. Overall tumour rate was 3.82 per 100 000 and did not change significantly over the study period. Hepatitis B‐associated cases decreased significantly over the study period ( P = 0.048) and were eliminated in persons under the age of 20. Hepatitis C‐associated cases increased significantly ( P < 0.001). Undetermined hepatocellular carcinoma rates also decreased ( P = 0.034). Conclusions: Overall hepatocellular carcinoma rates in Alaska Native people remained stable over the study period, but the epidemiology and aetiology are changing. Two decades after routine hepatitis B immunization, the hepatocellular carcinoma age distribution has shifted to cases presenting later in life. This is consistent with an ageing hepatitis B‐infected population with no new infected young persons' coming into the population, as well as the emergence of hepatitis C in adults.